2023
DOI: 10.14393/bj-v39n0a2023-67616
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial efficacy of Lactobacillus plantarum strain against the B. cereus, B. subtilis, S. aureus and E.coli strains

Abstract: The current study aimed to detect the antimicrobial effect of cell free supernatant (CFS) of Lactobacillus plantarum strain against Gram +ve and Gram –ve bacterial strains. The strain of Lactobacillus plantarum was isolated using selective media MRS agar. The strain was characterized on the basis of the gram staining, colony morphology, the biochemical tests and the DNA sequencing based method of 16S ribotyping. A total of four test strains (The three already isolated and reported strains (E.coli, S. aureus an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…In contrast, a significant decrease in antimicrobial activity (from 22.35 mm of original halo size) was observed when acidifying or neutralizing the CFS of L. plantarum CNTA 600. This agrees with the results reported by Akhtar and Syed [54] for a L. plantarum strain isolated from yogurt. The CFS from B. subtilis significantly decreased its native antimicrobial activity (28.52 mm) under acidic conditions, similar to what was previously observed by Epparti et al [75].…”
Section: Strainsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, a significant decrease in antimicrobial activity (from 22.35 mm of original halo size) was observed when acidifying or neutralizing the CFS of L. plantarum CNTA 600. This agrees with the results reported by Akhtar and Syed [54] for a L. plantarum strain isolated from yogurt. The CFS from B. subtilis significantly decreased its native antimicrobial activity (28.52 mm) under acidic conditions, similar to what was previously observed by Epparti et al [75].…”
Section: Strainsupporting
confidence: 93%
“…Similarly, the CFS of the selected strain L. plantarum CNTA 600 exhibited a strong antimicrobial effect against L. monocytogenes (15.27 ± 0.47 mm), consistent with the findings of Vataščinová et al [53]. A medium antimicrobial activity against B. cereus (13.36 ± 0.67 mm) was observed, corroborating similar previous results by Akhtar and Syed [54]. L. brevis CNTA 1374 CFS showed no antimicrobial activity against any of the pathogenic strains.…”
Section: Antimicrobial Activity Of the Cfssupporting
confidence: 91%
“…the left to the right side of the plot); the panelists highlighted the worst quality of samples after 28 days of storage, while after 21 days, some samples still were acceptable, i.e., MAP packaged samples were similar to the same samples at T14, which still had good characteristics, and were very different from Ctr. These outcomes revealed that MAP alone or in combination with protective starter, whose bacteriocins have been demonstrated to have antimicrobial activity against a wide range of bacteria [58][59][60], better preserved the sensory characteristics of burrata in agreement with VOC and the other chemicals results. In sum, the overall characteristics decrease over time for almost all products (from the left to the right side of the plot); the panelists highlighted the worst quality of samples after 28 days of storage, while after 21 days, some samples still were acceptable, i.e., MAP packaged samples were similar to the same samples at T14, which still had good characteristics, and were very different from Ctr.…”
Section: Resultsmentioning
confidence: 63%
“…In sum, the overall characteristics decrease over time for almost all products (from the left to the right side of the plot); the panelists highlighted the worst quality of samples after 28 days of storage, while after 21 days, some samples still were acceptable, i.e., MAP packaged samples were similar to the same samples at T14, which still had good characteristics, and were very different from Ctr. These outcomes revealed that MAP alone or in combination with protective starter, whose bacteriocins have been demonstrated to have antimicrobial activity against a wide range of bacteria [58][59][60], better preserved the sensory characteristics of burrata in agreement with VOC and the other chemicals results.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation